2013
DOI: 10.1590/s0036-46652013000600001
|View full text |Cite
|
Sign up to set email alerts
|

FIRST REPORT ON Cryptococcus neoformans IN PIGEON EXCRETA FROM PUBLIC AND RESIDENTIAL LOCATIONS IN THE METROPOLITAN AREA OF CUIABÁ, STATE OF MATO GROSSO, BRAZIL

Abstract: SUMMARYCryptococcosis is a severe systemic mycosis caused by two species of Cryptococcus that affect humans and animals: C. neoformans and C. gattii. Cosmopolitan and emergent, the mycosis results from the interaction between a susceptible host and the environment. The occurrence of C. neoformans was evaluated in 122 samples of dried pigeon excreta collected in 49 locations in the City of Cuiabá, State of Mato Grosso, Brazil, including public squares (n = 5), churches (n = 4), educational institutions (n = 3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
15
0
5
Order By: Relevance
“…concentration in the soil, air and trees. 14 Although pigeons are not natural carriers of C. neoformans s.l., 52 this fungus is commonly found as saprophyte in pigeon droppings 25,28 and other bird droppings, 53 particularly after it has dried. 23,53,54 Also, Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…concentration in the soil, air and trees. 14 Although pigeons are not natural carriers of C. neoformans s.l., 52 this fungus is commonly found as saprophyte in pigeon droppings 25,28 and other bird droppings, 53 particularly after it has dried. 23,53,54 Also, Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…1 Thus, many researchers have highlighted the occurrence of C. neoformans/C. gattii species complexes in the urban environment, 24,25,27,28 but none have studied the geographical correlation between classical C. neoformans/C. gattii species complex niches and cases of cryptococcal meningitis.…”
mentioning
confidence: 99%
“…From the analyzed samples, 7.69% (15) were positive for the capsulated yeast. In Cuiabá-MT, Takahara (2013) reported the occurrence of 6.6% C. neoformans in 122 samples of dry pigeon excreta collected in 49 locations in the city. Correa et al (2011) found 100% positive samples for C. neoformans in excreta from Columba sp.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have already shown the isolation of virulent strains of Cryptococcus spp. from excrement and soil samples in public areas (Reolon et al., ; Takahara et al., ; Yamamura, Freire, Yamamura, Felix, & Taroda, ) and also from the faeces of bats collected in abandoned houses (Lazéra et al., ). In the northern region of Brazil, there has been a report of a death due to cryptococcal meningitis, with bat faeces as the probable source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cryptococcus spp. worldwide are generally associated with bird droppings, mainly from pigeons (Abegg et al., ; Ellabib et al., ; Takahara et al., ). A possible explanation for the low rate of Cryptococcus spp.…”
Section: Discussionmentioning
confidence: 99%